Some Paranormed Double Difference Sequence Spaces for Orlicz Functions and Bounded-Regular Matrices - S. A. Mohiuddine; Kuldip Raj; Abdullah Alotaibi (Abstract and Applied Analysis)
The aim of this paper is to introduce some new double difference sequence spaces with the help of the Musielak-Orlicz function ℱ=(Fjk) and four-dimensional bounded-regular (shortly, RH-regular) matrices A=(anmjk). We also make an effort to study some topological properties and inclusion relations between these double difference sequence spaces.